Clean : overcoming addiction and ending America's greatest tragedy - Sheff, David (Houghton Mifflin Harcourt, 2013)
The author of the No. 1 New York Times bestseller "Beautiful Boy" offers a new paradigm for dealing with addiction based on cutting-edge research and stories of his own and other families' struggles with -- and triumphs over -- drug abuse.